Binding affinities of structurally related human rhinovirus capsid-binding compounds are related to their activities against human rhinovirus type 14. - Fox, M P (1991)
The binding affinities (Kds) and the rates of association and dissociation of members of a chemical class of antiviral compounds at their active sites in human rhinovirus type 14 (HRV-14) were determined. On the basis of analysis by LIGAND, a nonlinear curve-fitting program, of saturation binding experiments with HRV-14, the Kds for Win 52084, Win 56590, disoxaril (Win 51711), and Win 54954 were found to be 0.02, 0.02, 0.08, and 0.22 microM, respectively. The independently determined kinetic rates of association and dissociation resulted in calculated Kd values which were in agreement with the Kd values determined in saturation binding experiments. Scatchard plots of each of four compounds for the binding data indicated that approximately 40 to 60 molecules were bound per HRV-14 virion. Hill plots showed no evidence of cooperativity in binding. Furthermore, the antiviral activities (MICs in plaque reduction assays with HRV-14) for this limited series of compounds (n = 4) correlated well (r = 0.997) with the observed Kds. Likewise, the absence of detectable binding of Win 54954 to the drug-resistant mutant HRV-14 (Leu-1188) corresponded to a lack of antiviral activity. The positive relationship between the antiviral activities and the Kds that were determined may have implications for the molecular design of capsid-binding antirhinovirus drugs.